2018
DOI: 10.1007/978-3-030-01219-9_5
|View full text |Cite
|
Sign up to set email alerts
|

Materials for Masses: SVBRDF Acquisition with a Single Mobile Phone Image

Abstract: We propose a material acquisition approach to recover the spatially-varying BRDF and normal map of a near-planar surface from a single image captured by a handheld mobile phone camera. Our method images the surface under arbitrary environment lighting with the flash turned on, thereby avoiding shadows while simultaneously capturing highfrequency specular highlights. We train a CNN to regress an SVBRDF and surface normals from this image. Our network is trained using a large-scale SVBRDF dataset and designed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
129
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(129 citation statements)
references
References 44 publications
0
129
0
Order By: Relevance
“…For example, it is shown that depth and normals may be estimated from a single image [6,7,50] or multiple images [38]. Parametric BRDF may be estimated either from an RGBD sequence of an object [25,15] or for planar surfaces [21]. Lighting may also be estimated from images, either as an environment map [8,10], or spherical harmonics [48] or point lights [46].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is shown that depth and normals may be estimated from a single image [6,7,50] or multiple images [38]. Parametric BRDF may be estimated either from an RGBD sequence of an object [25,15] or for planar surfaces [21]. Lighting may also be estimated from images, either as an environment map [8,10], or spherical harmonics [48] or point lights [46].…”
Section: Related Workmentioning
confidence: 99%
“…Second, inverse rendering of a scene is particularly challenging, compared to single objects, due to complex appearance effects (e.g., inter-reflection, cast shadows, near-field illumination, and realistic shading). Some existing works [8,21,47,19] Li [19] PBRS [46] Gardner [8] Inverse Rendering Network (IRN) Input Image…”
Section: Introductionmentioning
confidence: 99%
“…A number of methods have been proposed that rely on deep learning to estimate the reflectance properties and meso‐structure from a single photograph under flash lighting [DAD∗18, LSC18, AAL16, LXR∗18] or under natural lighting [LDPT17, YLD∗18]. While promising, these methods either control the incident lighting, and/or are limited to planar samples only.…”
Section: Related Workmentioning
confidence: 99%
“…Several research projects address materials and their appearance in images. Georgoulis et al [14] use synthetic images of specular objects as training data to estimate reflectance and illumination, Li et al [19] recover the SVBRDF of a material also using rendered training data, and Yang et al [30] use synthetic images containing metal and rubber materials as training data for visual recognition. These authors however do not consider segmentation.…”
Section: Related Workmentioning
confidence: 99%